Fetal fibronectin, cervical length, and the risk of preterm birth in patients with an ultrasound or physical exam indicated cervical cerclage. (16th November 2016) - Kim, Renita S.; Gupta, Simi; Lam-Rachlin, Jennifer; Saltzman, Daniel H.; Rebarber, Andrei; Fox, Nathan S.
Abstract: Objective : The objective of this study is to estimate the risk of preterm birth in patients with an ultrasound or physical exam indicated cervical cerclage based on the results of fetal fibronectin (fFN) and cervical length (CL) screening. Methods : Retrospective cohort of patients with a singleton pregnancy and an ultrasound or physical exam indicated Shirodkar cerclage placed by one maternal–fetal medicine practice from November 2005 to January 2015. Patients routinely underwent serial CL and fFN testing from 22 to 32 weeks. Based on ROC curve analysis, a short CL was defined as ≤15 mm. All fFN and CL results included are from after the cerclage placement. Results : One hundred and four patients were included. Seventy eight (75%) patients had an ultrasound-indicated cerclage and 26 (25%) patients had a physical exam-indicated cerclage. A positive fFN was associate with preterm birth <32 weeks (15.6% versus 4.2%, p  = 0.043),  <35 weeks (37.5% versus 11.1%, p  = 0.002),  <37 weeks (65.6% versus 20.8%, p  < 0.001), and earlier gestational ages at delivery (35.2 ± 3.9 versus 37.4 ± 2.9, p  = 0.001). A short CL was also associated with preterm birth <35 weeks (50.0% versus 11.9%, p  < 0.01), preterm birth <37 weeks (55.0% versus 29.8%, p  = 0.033), and earlier gestational ages at delivery (34.8 ± 4.1 versus 37.2 ± 3.0, p  = 0.004). The risk of preterm birth <32,  <35, and <37 weeks increased significantly with the number of abnormal markers. Conclusion : In patients with an ultrasound or physical exam indicated cerclage, a positive fFN and a short CL are both associated with preterm birth. The risk of preterm birth increases with the number of abnormal biomarkers.